INFLUENCE OF GREEN OPERATIONS STRATEGY ON PERFORMANCE OF TEA PROCESSING FIRMS IN KENYA - Syanda, Kennedy Kyalo; Getuno, Dr. Pamela (International Journal of Supply Chain and Logistics, 2019)
Purpose: The study sought to establish the influence of green operations strategy on performance of tea processing firms in Kenya. Methodology: This research study adopted a descriptive research design approach. The researcher preferred this method because it allowed an in-depth study of the subject. The target population was heads of procurement and heads of finance in the 66 tea processing firms in Kenya. The study conducted a census since the number of respondents was less than 200, which is a rule of the thumb. The study combined two methods in its data collection, that is, questionnaires and key informant interviews. After data collection, quantitative data was coded using Statistical Package for Social Science (SPSS) version 20. Results: The independent variables reported R value of 0.846 indicating that there was perfect relationship between dependent variable and independent variables. R square value of 0.715 means that 71.5% of the corresponding variation in performance of tea processing firms can be explained or predicted by (green product design, green distribution and transportation, green warehousing and reverse logistics) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î² = 0.715), p=0.000 <0.05). Conclusion: The findings of the study indicated that green product design, green distribution and transportation, green warehousing and reverse logistics have a positive relationship with performance of tea processing firms. Policy recommendation: The study recommends that tea processing firms should embrace green operations strategy so as to improve performance and further researches should to be carried out in other institutions to find out if the same results can be obtained.